2018
DOI: 10.3389/fendo.2018.00722
|View full text |Cite
|
Sign up to set email alerts
|

3D Facial Analysis in Acromegaly: Gender-Specific Features and Clinical Correlations

Abstract: Objective: Quantitative investigations of facial changes in acromegaly are rare. A new imaging technique, three-dimensional (3D) stereophotography, can accurately quantify whole facial changes. We aimed to measure facial characteristics in acromegaly patients using 3D stereophotography, analyze gender-specific features, and explore clinical influencing factors.Design: Single-center case-control study.Methods: Thirty-nine acromegaly patients and 39 age- and gender-matched healthy subjects were prospectively enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…To the best of our knowledge, there are no studies performing a longitudinal evaluation of these modi cations over time. We found greater facial morphometric differences in men than in women, especially in the post-diagnosis phase, as also evidenced by different reports, which con rm that the morphometric progression is irreversible and show a sexual dimorphism [21,23,24]. Likewise, other ndings con rm that morphometric modi cations remained signi cantly altered two years after remission in cured patients [25,26], as we did in the present work.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, there are no studies performing a longitudinal evaluation of these modi cations over time. We found greater facial morphometric differences in men than in women, especially in the post-diagnosis phase, as also evidenced by different reports, which con rm that the morphometric progression is irreversible and show a sexual dimorphism [21,23,24]. Likewise, other ndings con rm that morphometric modi cations remained signi cantly altered two years after remission in cured patients [25,26], as we did in the present work.…”
Section: Discussionsupporting
confidence: 90%
“…In the research group's previous study, references were made from the existing literature to preliminarily select 14 basic facial parameters that can be used to characterize the facial contour, nose, and lips, before making precise measurements using 3D imaging, and analyzing their correlations with hormone levels ( 16 ). Because of the complexity and diversity of facial information, 3D imaging was further used in this study to comprehensively mine the facial information available in more subjects, and analyze their internal correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas certain authors did not find, similar to us, any gender-related differences (12), others found a lower Qol in women (18,28). An interesting study using 3D facial analysis stereophotography showed that men are more at risk to develop dysmorphic facial features, with more pronounced nose width, length and depth, face length, width, gonion-gnathion distances and nasofrontal and columella-labial angles (29). Despite these morphological findings, Qol seems to be significantly hampered to at least the same extent in both genders, if not even more in women.…”
Section: Discussionmentioning
confidence: 99%